Association between weight-adjusted waist index and 20-meter shuttle run test in Chinese children and adolescents: a multicenter cross-sectional survey - Zhang, Zhen; Tang, Nana; Yao, Mengjin; Zhao, Zhimin (Frontiers in Public Health, 2025)
BackgroundCardiopulmonary fitness is associated with several physical health indicators in children and adolescents and has shown a downward trend in recent years. The 20-m SRT has received widespread attention from scholars as a recognized indirect measure for evaluating cardiopulmonary fitness. However, few studies have analyzed the association between the weight-adjusted waist index (WWI), a novel indicator, and cardiopulmonary fitness in Chinese children and adolescents.MethodsIn this study, 41,523 children and adolescents aged 6–17 years in China were assessed for weight, waist circumference, 20-m SRT, and related covariates. One-way ANOVA, LSD, and curvilinear regression analyses were used to analyze the associations that existed between WWI and 20-m SRT.ResultsComparison of WWI and 20-m SRT scores among Chinese children and adolescents of different ages showed statistically significant differences (F-values of 2179.297 and 4956.795, respectively, p < 0.001). Overall, the 20-m SRT scores of both boys and girls showed a general trend of increasing with age, with a maximum of 48.78 laps and 31.17 laps in the age group of 15–17 years, respectively. The differences in 20-m SRT scores were statistically significant (p < 0.001) when compared between different WWI groups. Both lower and higher WWI resulted in lower 20-m SRT scores, more significantly in boys compared to girls.ConclusionThere is an inverted “U” curve relationship between WWI and 20-m SRT in Chinese children and adolescents aged 6–17 years, and this relationship is reflected in different genders and age groups. In the future, we should ensure that the WWI of children and adolescents is within a reasonable range to better promote cardiopulmonary fitness.